Äänen syvä ymmärtäminen: harmoninen laulu kulttuureja yhdistävänä ja kasvuun tähtäävänä metodina - Korpelin, Jani (2016)
The research consisted of the philosophical-historical part and the theoretical methodology of the part. A qualitative research was conducted through theme interviews and participatory observation.